2016
DOI: 10.1177/1359105315624750
|View full text |Cite
|
Sign up to set email alerts
|

Public perceptions of personalised nutrition through the lens of Social Cognitive Theory

Abstract: Social Cognitive Theory (SCT) has been used to explain findings derived from focus group discussions (N=4) held in the UK with the aim of informing best practice in personalised nutrition. Positive expectancies included weight loss and negative expectancies surrounded on-line security. Monitoring and feedback was crucial to goal setting and progress. Coaching by the service provider, family and friends was deemed important for self-efficacy. Paying symbolised commitment to behaviour change. The social context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 23 publications
(50 reference statements)
3
25
0
1
Order By: Relevance
“…'s very motivational" (FG2, Canada) This aligns with previous research which found that personalised information improved healthy eating indices (Celis-Morales et al, 2016) and adherence to a Mediterraneantype dietary pattern (Livingstone et al, 2016). Diffusion theory holds that aspects of the technology such as observability of results, is important for its adoption (Ronteltap et al, 2007). Using nutrigenomic testing with clients was perceived by the RD's to enhance their confidence, render them more engaged as therapists and enable "different" practice.…”
Section: Experiences Of Ngx In Practice: Becoming Empowered and Engagedsupporting
confidence: 69%
See 3 more Smart Citations
“…'s very motivational" (FG2, Canada) This aligns with previous research which found that personalised information improved healthy eating indices (Celis-Morales et al, 2016) and adherence to a Mediterraneantype dietary pattern (Livingstone et al, 2016). Diffusion theory holds that aspects of the technology such as observability of results, is important for its adoption (Ronteltap et al, 2007). Using nutrigenomic testing with clients was perceived by the RD's to enhance their confidence, render them more engaged as therapists and enable "different" practice.…”
Section: Experiences Of Ngx In Practice: Becoming Empowered and Engagedsupporting
confidence: 69%
“…This perspective fits with diffusion theory which holds that characteristics of the technology pertinent to adoption are likely to be related to its perceived efficacy (Ronteltap et al, 2007).…”
Section: "And Then Some People Just Really Not Knowing What It's Aboumentioning
confidence: 66%
See 2 more Smart Citations
“…*Provide incentive for those in Netherlands to take up PN. Rankin et al, 2016 United Table 5: Perceived benefits of the uptake of personalised nutrition -factor structure, factor loadings and % variance explained Table 6: Perceived benefit and barriers (data protection; family/social; trust in agencies) to the uptake of personalised nutrition -factor mean (M) and standard deviation (SD) …”
Section: Referencesmentioning
confidence: 99%